Modern chemical enhanced oil recovery theory and practice - Sheng, James (Gulf Professional Pub., 2011)
Crude oil development and production in U.S. oil reservoirs can include up to three distinct phases: primary, secondary, and tertiary (or enhanced) recovery. During primary recovery, the natural pressure of the reservoir or gravity drive oil into the wellbore, combined with artificial lift techniques (such as pumps) which bring the oil to the surface. But only about 10 percent of a reservoir's original oil in place is typically produced during primary recovery. Secondary recovery techniques to the field's productive life generally by injecting water or gas to displace oil and drive it to a pro.
Keywords: Enhanced oil recovery.; Oil reservoir engineering.; Oil fields -- Production methods.; elektronické knihy; electronic books